TENG-TENGAN TRADITION , KETUWINAN AND WEH-WEHAN IN KALIWUNGU, KENDAL, CENTRAL JAVA (Study of Living Hadith with Symbolic Interpretive Anthropology Approach) - Hamzah, Ghufron; Achmad, Noor; Istibsaroh, Istibsaroh; Sa'adah, Nailis (Pascasarjana Universitas Wahid hasyim Semarang, 2022)
Tradition is a continuous activity carried out by a social community that has been running for a very long time. Including the traditions of teng- tengan , ketuwinan and weh-wehan in Kaliwungu. This research was conducted to find out the history and implementation of the tradition. First, how the origins and traditions are carried out, Second, the relevance of the study of living hadith with a symbolic interpretive anthropology approach in viewing the teng-tengan, ketuwinan and weh-wehan traditions in Kaliwungu. The method of data collection is done through observation, interviews, and documentation including references relevant to the study. While the data analysis used is descriptive qualitative with a symbolic interpretive anthropological approach. According to Geertz, the happy expression symbolized in the teng- tengan tradition is because religion affects mood and motivation / creates strong feelings and motivations for its adherents and in the end these feelings and motivations will be seen as a unique reality, a hereditary tradition. Symbols in the form of physical ( teng-tengan / lanterns ) as well as symbols in the form of actions ( ketuwinan and weh-wehan) this tradition is full of actualization of informative and performative values of normative teachings about the virtues of the Prophet Muhammad . Keywords: Teng-tengan Tradition, Ketuwinan and Weh-wehan, Living Hadith, Symbolic Interpretive Anthropology